2004
DOI: 10.1161/01.str.0000131903.04708.b8
|View full text |Cite
|
Sign up to set email alerts
|

Ethnic Differences in Risk Factors for Ischemic Stroke

Abstract: Background and Purpose-The aim is to estimate the relative risk and population attributable risk (PAR) of risk factors for ischemic stroke by ethnic group. Methods-In this case-control study, cases of first ischemic stroke were taken from the South London Stroke Register and controls from a cross-sectional prevalence survey covering the same area. PAR was determined for each risk factor by ethnic group. Multivariable analysis was used to examine the association between risk factors and ischemic stroke across a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
39
2
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(48 citation statements)
references
References 17 publications
(34 reference statements)
6
39
2
1
Order By: Relevance
“…There are reports contributing the different global burden of vascular diseases in different population to the ethnic and regional variations in cardiovascular risk factors [6][7][8][9]. The above-mentioned facts prompted several investigators to conduct studies on types and distribution modes of traditional and newly recognized risk factors in different populations [10,11] including lipid and lipoproteins indices [12].…”
Section: Introductionmentioning
confidence: 99%
“…There are reports contributing the different global burden of vascular diseases in different population to the ethnic and regional variations in cardiovascular risk factors [6][7][8][9]. The above-mentioned facts prompted several investigators to conduct studies on types and distribution modes of traditional and newly recognized risk factors in different populations [10,11] including lipid and lipoproteins indices [12].…”
Section: Introductionmentioning
confidence: 99%
“…A population study in South London demonstrated that ethnic differences exist in patterns of behavioral risk factors between black Africans (BAs) and black Caribbeans (BCs), with a greater proportion of BAs, for example, having never smoked and a smaller proportion with a heavy alcohol intake compared with BCs. 8 Data are lacking on the relation between risk factors and stroke risk for particular ethnic groups.…”
mentioning
confidence: 99%
“…Such variations in both CHD and stroke incidence and prevalence are largely explained by area-and person-specific factors such as population socio-economic composition, demographic structure and ethnic diversity [1][2][3][4], mediated through established CVD risk factors [5]. In the case of England, this is exemplified at a regional level by a North-South gradient in prevalence and outcomes, with higher prevalences in the North [6].…”
Section: Introductionmentioning
confidence: 99%